Minimizing Air Pollution by Planting Plants in Recyclable Plastic Bottles in Bestlink College of the Philippines (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Air is important to people’s daily lives. Without air, people cannot live even for a second, they will not be able to breathe, and they will die. At present, one of the primary problems in daily life is air pollution. People inhale and exhale polluted air every day. Air pollution refers to the release of pollutants into the air that is detrimental to human health and the planet as above. The research focused on minimizing air pollution by planting plants in recyclable plastic bottles. The study wants to give action on how to minimize air pollution and lessen the plastic bottles litter everywhere. Planting in recyclable plastic bottles can minimize air pollution with a unity of people, participation, and cooperation for this activity to solve not only air pollution but also the recycling manner and proper littering of plastic bottles of individuals. The method used in the study was the qualitative method by using a descriptive research design. This study involved 50 selected grade 12 Accountancy, Business, and Management Strandstudents at Bestlink College of the Philippines. Variables such as smokes, deforestation, good ambiance of an environment, students’ responsibility, proper plastic disposal, and fresh air inside the campus are the major factors that affect the good ambiance of the environment. Most of the students agreed that they must be responsible for the life of their plants, and students can participate in separating plastic bottles from other wastes according to their classification. The students agreed to implement planting plants in recyclable plastic bottles for the cleanliness of the environment, the good ambiance of the classroom, for them to be responsible, to have fresh air inside of campus, and to have surroundings that at pleasing to the eyes. The results of this study revealed that the major causes of air pollution are smoke and deforestation. In addition to the fact that fresh air will give a good ambiance to the room, students may become more responsible in taking good care of the plants, and they can participate in the proper disposal of plastic bottles. The students agreed to implement planting plants in recyclable plastic bottles for the cleanliness of the environment, the good ambiance of the classroom, students’ responsibility, fresh air inside of campus, and surroundings that are pleasing to the eyes.
Keywords: air pollution, segregation